A small unmanned aerial system for estimating abundance and size of Antarctic predators - Goebel, Michael E.; Perryman, Wayne L.; Hinke, Jefferson T.; Krause, Douglas J.; Hann, Nancy A.; Gardner, Steve; LeRoi, Donald J. (Polar biology, 2015)
Quantifying the distribution and abundance of predators is integral to many ecological studies, but can be difficult in remote settings such as Antarctica. Recent advances in the development of unmanned aerial systems (UAS), particularly vertical takeoff and landing (VTOL) aircraft, have provided a new tool for studying the distribution and abundance of predator populations. We detail our experience and testing in selecting a VTOL platform for use in remote, windy, perennially overcast settings, where acquiring cloud-free high-resolution satellite images is often impractical. We present results from the first use of VTOLs for estimating abundance, colony area, and density of krill-dependent predators in Antarctica, based upon 65 missions flown in 2010/2011 ( n = 28) and 2012/2013 ( n = 37). We address concerns over UAS sound affecting wildlife by comparing VTOL-generated noise to ambient and penguin-generated sound. We also report on the utility of VTOLs for missions other than abundance and distribution, namely to estimate size of individual leopard seals. Several characteristics of small, battery-powered VTOLs make them particularly useful in wildlife applications: (1) portability, (2) stability in flight, (3) limited launch area requirements, (4) safety, and (5) limited sound when compared to fixed-wing and internal combustion engine aircraft. We conclude that of the numerous UAS available, electric VTOLs are among the most promising for ecological applications.